CONTRIBUTION OF AGRICULTURAL OUTPUT TO NIGERIA’S CONSTANT BASIC PRICE GDP: A PANEL DATA REGRESSION APPROACH - Adams, Samuel Olorunfemi; Obonyilo, Blessing Adunyi; Kolawole, Timileyin Babalola (FUDMA JOURNAL OF SCIENCES, 2024)
This study focuses on contribution of agricultural output from crop production, livestock, fishing and forestry on Nigeria’s GDP contact basic prices. The study aimed to conduct a panel data analysis of Agricultural outputs and the constant basic prices of selected economic sectors in Nigeria. This study examined the impact of crop output, livestock, fisheries, and forestry on Nigeria’s constant price GDP, using numerous components of Nigeria’s GDP as cross-sectional data. To achieve these goals, secondary data for crop output, livestock, fishery, forestry, and GDP constant basic price were gathered from the National Bureau of Statistics (NBS) website from Q1 2010 to Q4 2023. This study utilized panel data estimating, which clearly accounts for variation and examines the parameter’s dynamic behavior. The research results show that crop output has a considerable positive effect on GDP, whereas additional agricultural goods such as farm animals, forest products, and fishery have a minor beneficial effect on GDP with correlations. The results also revealed that cereal production and livestock comprise approximately 40.62% and 35.66% of Nigeria’s GDP, respectively, with the remaining proportion unexplainable due to the presence of a stochastic error factor. It is proposed that sub-sectors that contribute insignificantly to GDP at constant basic prices be enhanced in order to have a substantial impact on GDP and encourage the development and expansion of the Nigerian economy.